1993
DOI: 10.1111/1523-1747.ep12470147
|View full text |Cite
|
Sign up to set email alerts
|

Non-Melanosomal Regulatory Factors in Melanogenesis.

Abstract: The enzyme activity of tyrosinase, catalase, and peroxidase and the number of metal ions in melanogenic subcellular compartments in pigment cells were measured. Coated vesicles were richest in tyrosinase and catalase, whereas premelanosomes had the highest amount of peroxidase. Among metals ions examined, copper, zinc, and iron were more concentrated in pre-melanosomes than in coated vesicles. A quantitative analysis revealed that peroxidase served to enhance eumelanin polymer formation from monomers in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…CRH, ACTH, MSH and β-endorphins clearly play a melanogenic function Kauser et al 2004;2005;Hirobe 2005;Paus 2011), while serotonin (O'Malley 1960; Slominski et al 2004), dopamine (Slominski et al 2004), adrenaline and noradrenaline (O'Malley 1960) exert an inhibiting effect on melanogenesis. Regarding corticosteroids, some authors are of the opinion that they stimulate the biosynthesis of melanin (Shibata et al 1993), while others have demonstrated their depigmentation effects (Arnold et al 1975).…”
Section: Lerner Cited In Slominski 2009)mentioning
confidence: 99%
“…CRH, ACTH, MSH and β-endorphins clearly play a melanogenic function Kauser et al 2004;2005;Hirobe 2005;Paus 2011), while serotonin (O'Malley 1960; Slominski et al 2004), dopamine (Slominski et al 2004), adrenaline and noradrenaline (O'Malley 1960) exert an inhibiting effect on melanogenesis. Regarding corticosteroids, some authors are of the opinion that they stimulate the biosynthesis of melanin (Shibata et al 1993), while others have demonstrated their depigmentation effects (Arnold et al 1975).…”
Section: Lerner Cited In Slominski 2009)mentioning
confidence: 99%
“…A third enzymatic role has been proposed for tyrosinase: the oxidation of 5,6-dihydroxyindole to 5,6-dihydroxyquinone [22,24]. However, it has also been proposed that this oxidation is performed through a peroxidase [25]. Tyrosinase preparations are enzymatically active at a pH range of 5-8, but in vivo the enzyme might encounter even lower values due to the acidic intramelanosomal pH [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these steps include the oxidation of DOPA [16, 17], the oxidative polymerization of indolic melanin monomers to eumelanin [18], and the polymerization of benzothiazine type intermediates to pheomelanin [19, 20]. The inhibition of peroxidase by MMI could interfere with melanin synthesis at different steps, explaining its depigmenting action on the skin.…”
Section: Discussionmentioning
confidence: 99%